2007
DOI: 10.1038/msb4100159
|View full text |Cite
|
Sign up to set email alerts
|

Ubiquitination screen using protein microarrays for comprehensive identification of Rsp5 substrates in yeast

Abstract: Ubiquitin-protein ligases (E3s) are responsible for target recognition and regulate stability, localization or function of their substrates. However, the substrates of most E3 enzymes remain unknown. Here, we describe the development of a novel proteomic in vitro ubiquitination screen using a protein microarray platform that can be utilized for the discovery of substrates for E3 ligases on a global scale. Using the yeast E3 Rsp5 as a test system to identify its substrates on a yeast protein microarray that cov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
154
1
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 153 publications
(164 citation statements)
references
References 70 publications
7
154
1
2
Order By: Relevance
“…These data confirm the existence of ubiquitylation sites on Bul1 and Bul2 and suggest that these residues may play a role in Rsp5-dependent regulation of plasma membrane proteins. Notably, two other arrestins, Ecm21/Art2 and Art10, are also ubiquitylated by Rsp5 (54,55), and we detected decreased ubiquitylation of specific residues in tul1⌬ cells (Ecm21/Art2 K95, H/L ϭ 1.5; Art10 K118, H/L ϭ 1.6). However, analysis of ubiquitylation for all 10 Art proteins revealed that Tul1-dependent ubiquitylation of arrestins was limited to Ecm21/Art2 and Art10 (supplemental Table S5).…”
Section: Tul1 E3 Ligase Subunit Genes Show Genetic Interactions With mentioning
confidence: 69%
“…These data confirm the existence of ubiquitylation sites on Bul1 and Bul2 and suggest that these residues may play a role in Rsp5-dependent regulation of plasma membrane proteins. Notably, two other arrestins, Ecm21/Art2 and Art10, are also ubiquitylated by Rsp5 (54,55), and we detected decreased ubiquitylation of specific residues in tul1⌬ cells (Ecm21/Art2 K95, H/L ϭ 1.5; Art10 K118, H/L ϭ 1.6). However, analysis of ubiquitylation for all 10 Art proteins revealed that Tul1-dependent ubiquitylation of arrestins was limited to Ecm21/Art2 and Art10 (supplemental Table S5).…”
Section: Tul1 E3 Ligase Subunit Genes Show Genetic Interactions With mentioning
confidence: 69%
“…3). Unlike known Nedd4-1 substrates, including LAPTM5, which typically contain PY motifs (27)(28)(29)(30)32), PTEN does not possess this motif, possibly explaining the observed lack of its interaction with Nedd4-1 ( Fig. 3 C and D) and unaffected PTEN ubiquitination in Nedd4-1-deficient cells (Fig.…”
Section: Discussionmentioning
confidence: 96%
“…The WW domain of Nedd4 proteins recognizes and binds a short amino acid sequence in substrate proteins, called the PY motif (L/PPxY) (26)(27)(28)(29)(30). By using two independent approaches, we recently generated distinct strains of mice with disrupted Nedd4-1 gene, leading to a complete loss of Nedd4-1 protein and embryonic lethality at mid to late gestation (F.F.…”
mentioning
confidence: 99%
“…To further characterize the structural determinants necessary for Gpa1 mono-ubiquitination, we examined the protein for potential Rsp5 docking sites. Rsp5 contains WW protein interaction domains that bind and recruit substrates or substrate adaptor proteins containing one or more short PY motifs (PPXY) within their primary structure (47,48). However, the PXY portion of the motif is the minimal FIGURE 5.…”
Section: Gpa1 Protein Folding Mutants Are Targeted For Poly-ubiquitinmentioning
confidence: 99%
“…requirement for establishing an interaction with Rsp5, whereas nonpolar hydrophobic residues can be tolerated at the first position of the motif (e.g. LPXY or APXY) (47,48). Gpa1 contains a single non-canonical PY motif (FPDY) that contains a nonpolar hydrophobic residue in position 1.…”
Section: Table 1 Relative Free Energies Of Gpa1 Protein Fold-destabilmentioning
confidence: 99%